Development of a Promising 18F-Radiotracer for PET Imaging Legumain Activity In Vivo - Chunmei Lu; Xiuting Wang; Qiqi Wang; Lixia Zhang; Jianguo Lin; Ling Qiu (MDPI AG, 2022)
Legumain has been found overexpressed in several cancers, which serves as an important biomarker for cancer diagnosis. In this research, a novel fluorine-18 labeled radioactive tracer [18F]SF-AAN targeting legumain was designed and synthesized for positron emission tomography (PET) imaging. Nonradioactive probe [19F]SF-AAN was obtained through chemical and solid phase peptide synthesis. After a simple one-step 18F labeling, the radiotracer [18F]SF-AAN was obtained with a high radiochemical conversion rate (>85%) and radiochemical purity (99%) as well as high molar activity (12.77 ± 0.50 MBq/nmol). The targeting specificity of [18F]SF-AAN for detecting legumain activity was investigated systematically in vitro and in vivo. In vitro cellular uptake assay showed that the uptake of [18F]SF-AAN in legumain-positive MDA-MB-468 cells was twice as much as that in legumain-negative PC-3 cells at 4 h. In vivo PET imaging revealed that the tumor uptake of [18F]SF-AAN in MDA-MB-468 tumor-bearing mice was about 2.7 times of that in PC-3 tumor-bearing mice at 10 min post injection. The experimental results indicated that [18F]SF-AAN could serve as a promising PET tracer for detecting the legumain expression sensitively and specifically, which would be beneficial for the diagnosis of legumain-related diseases.